Bovine colostrum in human health promotion: determinants and moderators of purchase intention and consumption in Brazil - GALDINO, Alyne Batista da Silva; ARAÚJO, Emmanuella de Oliveira Moura; RIBEIRO, Cláudio Vaz Di Mambro; CORDEIRO, Clarice Gebara Muraro Serrate; SANTOS, Geraldo Tadeu dos; SALES, Danielle Cavalcanti; MARQUES JÚNIOR, Sérgio; RANGEL, Adriano Henrique do Nascimento (Food Science and Technology, 2024)
This study aimed to investigate the perception of the Brazilian population about bovine colostrum and the perspectives of consumption and purchase of its derived foods. A questionnaire was made available on the Google Forms® platform and disseminated through social networks. A total of 1,179 people from 19 Brazilian states responded. Spearman’s test was used to identify correlations between variables, and the Kruskal–Wallis test was used to compare means. Correlation and difference of means were considered significant when p < 0.05. Most respondents (45.0%) reported having no knowledge about bovine colostrum and never having had contact with it (67.8%). However, they believe that consumption can benefit human health (61.6%). They also reported their intention to consume and purchase food and derived supplements in the form of dairy products, powdered supplements, and flavored liquid supplements. Sensory aspects can contribute to the non-consumption of bovine colostrum. However, a lack of knowledge about the products and their benefits, availability, and price can further influence the intention not to consume derivatives. Thus, it is likely that foods derived from bovine colostrum will be well accepted if commercialized in the Brazilian market.